2022
DOI: 10.1159/000525555
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Influencing Seroconversion after Inactive SARS-CoV-2 Vaccination in People Living with Obesity

Abstract: Introduction To investigate the antibody titers against SARS-CoV-2 spike antigens, and the risk factors affecting antibody levels in people living with obesity (PwO) after inactive SARS-CoV-2 vaccine (Corona Vac) administration. Methods 169 consecutive patients with obesity who visited the Center for Obesity Management at Istanbul University-Cerrahpaşa, Cerrahpaşa Medical Faculty Hospitals, between May and August 2021, were invited to the study. The non-obese control group was recruited from 191 subjects who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Obesity is a growing global public health concern, and individuals with obesity are at a higher risk of morbidity and mortality from COVID-19 ( 55 , 56 ). It has been observed that vaccination with CoronaVac results in lower levels of antibodies against the Spike protein in individuals with obesity compared to non-obese individuals ( 57 ). On the other hand, vaccination with BNT162b2 has been reported to have no impact on the magnitude of antibody titers against the RBD and neutralizing antibodies in obese individuals ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a growing global public health concern, and individuals with obesity are at a higher risk of morbidity and mortality from COVID-19 ( 55 , 56 ). It has been observed that vaccination with CoronaVac results in lower levels of antibodies against the Spike protein in individuals with obesity compared to non-obese individuals ( 57 ). On the other hand, vaccination with BNT162b2 has been reported to have no impact on the magnitude of antibody titers against the RBD and neutralizing antibodies in obese individuals ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is a wealth of evidence suggesting that obesity leads to perturbed immune responses with unfavourable outcomes, and thus it is not surprising that decreased seropositive convertion rates are common in obese individuals following vaccination. Specifically, poor antibody responses have been reported in obese individuals upon tetanus ( 70 ), influenza ( 66 , 71 ) or inactivated SARS-CoV-2 ( 72 ) vaccinations. In contrast, other vaccination regimes, such as live-attenuated hepatitis A, have been shown to be equally effective in both obese and lean individuals, suggesting that other factors may be at play ( 73 ).…”
Section: Systemic Metabolism and Vaccine Responsesmentioning
confidence: 99%
“…We would like to correspond on the publication "Risk factors influencing seroconversion after inactive SARS-CoV-2 vaccination in people living with obesity" [1]. People with obesity (PwO) had lower SARS-CoV-2 immunoglobulin G antibody levels against the inactive CoronaVac vaccine than people without obesity (PnP), according to Kara et al [1]. Additionally, Kara et al [1] stated that, for the best protection, booster doses should be administered in PwO based on determined antibody titers.…”
Section: Dear Editormentioning
confidence: 99%
“…People with obesity (PwO) had lower SARS-CoV-2 immunoglobulin G antibody levels against the inactive CoronaVac vaccine than people without obesity (PnP), according to Kara et al [1]. Additionally, Kara et al [1] stated that, for the best protection, booster doses should be administered in PwO based on determined antibody titers. Due to the hazards connected with COVID-19 and the wide range of clinical symptoms it may cause, vaccination is crucial for effective illness management.…”
Section: Dear Editormentioning
confidence: 99%